Building customer citizenship behavior through corporate social responsibility, perceived value, and perceived service quality: The mediating effect of corporate reputation - Jalal Rajeh Hanaysha; Abdallatif Abuowda (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2025)
This paper focuses on examining the effect of corporate social responsibility (CSR), perceived value, and perceived service quality on corporate reputation and customer citizenship behavior (CCB) in the airline industry. It further aimed to verify the mediating effect of corporate reputation among the aforementioned variables. This study adopted a quantitative research approach and a convenience sampling technique for data collection. Specifically, required data were collected through an online survey from 346 Airline passengers in the UAE. After data collection, partial least square structural equation modeling through SmartPLS 4 was used for analyzing the data. The findings showed that corporate reputation positively affects CCB. The analysis further revealed that CSR, perceived service quality and perceived value have positive effects on also corporate reputation as well as CCB. Finally, it was verified that corporate reputation mediates the link among the stated factors and customer citizenship behavior. These results enrich our knowledge about the factors that affect CCB in the airline industry. In addition, taking-into account the small number of studies that have been conducted previously about this topic in the Arab region, this article adds to the prevalent literature by investigating the influence of the selected factors on corporate reputation and customer citizenship behavior with empirical insights from the UAE.
Keywords: 330; airline industry; corporate reputation; Corporate social responsibility; customer citizenship behavior; perceived service quality; perceived value